A case of high drain output after renal transplantation: Review of current evidence - Sajid Mohmad; Ajay Sharma; Ahmed Halawa (Archives of Organ Transplantation - Peertechz Publications, 2018)
Surgical complications are not uncommon after renal transplantation. They should always be in the differential diagnosis of renal graft dysfunction. While ruling out or confirming a surgical cause of graft dysfunction, a sequential approach should be undertaken starting from clinical examination and moving on to more invasive investigations as the clinical picture becomes clearer. Biochemical assay of drain fluid is important. Causes of a collection around/near the graft include abscess, hematoma, urinoma and lymphocele. Treatment of each of them is different.  Causes of urinoma can be donor derived or surgical technique related. SPECT/CT may be needed to confirm the location of urinary leak. Treatment of the urinoma depends on its severity and location. Small and distal lesions can be treated conservatively while as larger and proximal leaks need surgical intervention. Ureteric stenting may be undertaken as a prophylaxis against urinary leak. Lymphoceles should always be considered as a cause of perinephric collection in renal transplant. It can be differentiated from a urinoma by the concentration of creatinine in the drain fluid. The treatment may be conservative or surgical depending on the size of the lymphocele and initial response or resistance to conservative management.  Scenario: A 28-year-old CKD 5 underwent a kidney transplantation from his brother with primary function. Post-surgery, the drain is quite productive (820 mls on day 2 and 750 mls on day 3). Drain fluid biochemistry showed K of 28 mmol/L and creatinine of 16000 μmol/l. His serum creatinine on that day was 416 μmol/l and serum K is 5.1 mmol/L.